The Sentence Pattern Approach in Teaching the English Tenses: Problems in Achieving the Communicative Goals - Saunir Saun (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
The awareness of communicative teaching of English has been realized since long time ago. In Indonesia, the wish to make the communicative ability as a goal of the teaching English in our schools, both the junior high schools and senior high schools, can be traced back from the development of the school curricula from time to time. However, the ways or approaches used by many teachers seem not yet successful in making the students able to communicate. One of the possible drawbacks causing this “failure” is the inappropriate approach to teaching the English grammar, especially the tenses. This paper discusses the problems that may appear in teaching the English tenses in relation to achieving the communicative goals. The teaching of the tenses should not make the students find it difficult to use the language communicatively. The sentence pattern approach in teaching them can cause problems in achieving this goal.